2018
DOI: 10.1016/j.jtcvs.2017.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of image-guided video-assisted thoracoscopic surgery for small pulmonary nodules: A prospective analysis of 30 initial patients

Abstract: Our data demonstrate a significant learning curve for image-guided video-assisted thoracoscopic surgery in the treatment of solitary pulmonary nodules as evidenced by decreased localization time and radiation exposure occurring with increased surgical experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 16 publications
0
55
0
Order By: Relevance
“…4 In similar procedures using thoracoscopic techniques, it has been shown that surgeons need to perform at least 50 procedures to feel comfortable, with even higher case volumes needed to decrease operative times. 11,12 At Boston Children's Hospital, the case volume per surgeon was not sufficient to trend operative times against experience, but with more clinical data, it would not be unreasonable to expect shorter operative times. Taken together, our data and that reported in the literature suggest that increased utilisation may eliminate differences in operative time compared to thoracotomy, while preserving the benefits of shorter hospitalisations and ICU stays.…”
Section: Discussionmentioning
confidence: 99%
“…4 In similar procedures using thoracoscopic techniques, it has been shown that surgeons need to perform at least 50 procedures to feel comfortable, with even higher case volumes needed to decrease operative times. 11,12 At Boston Children's Hospital, the case volume per surgeon was not sufficient to trend operative times against experience, but with more clinical data, it would not be unreasonable to expect shorter operative times. Taken together, our data and that reported in the literature suggest that increased utilisation may eliminate differences in operative time compared to thoracotomy, while preserving the benefits of shorter hospitalisations and ICU stays.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had described image-guided video assisted thoracoscopic surgery with marking in real time, in single suite, and immediate resection in a hybrid operating room. Those trials summarized many advantages of iVATS, such as (1) iVATS provides a less invasive approach and results in less discomfort for patients and improved postoperative recovery and general satisfaction; (2) complete and minimal resection of early lung cancer with optimal margin, allowing maximal preservation of patients' lung volume and function; (3) single use of anesthesia and the use of only one room improve both perioperative outcomes (e.g., shorter operative duration and length of hospital stay) and general cost-effectiveness; and (4) iVATS encourages early cancer treatment (1)(2)(3)(4)(5)(6). However, none of these studies demonstrated the utility of iVATS for bilateral lung nodule resection.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the lack of a control group (performing bronchoscopic and CT-guided procedure separately) makes it difficult to differentiate the specific benefits of combining the workflows into one step. Third, the procedures were not well standardized in some parts, especially when performing needle localization, and more cases are necessary to overcome the learning curve of using the iGUIDE system (15). Further investigations are necessary to clarify the applicability and benefits of this new localization method.…”
Section: Discussionmentioning
confidence: 99%